CULTURAL DIVERSITY IN PANCASILA PHILOSOPHY: A CONTRIBUTION FOR SOCIAL AND NATIONAL IDENTITY AWARENESS - Nurdiyanti, Aina; Khaedir Hedir, Muhammad (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
Cultural diversity is a distinctive characteristic of Indonesian society, which consists of various ethnicities, religions, races, and groups. The philosophy of Pancasila, as the nation's foundational ideology, functions to unite these differences into a harmonious whole. This article aims to explore how Pancasila values support social understanding and the formation of national identity within the framework of cultural diversity. Using a qualitative approach and literature review method, this article examines the role of Pancasila in maintaining harmony amidst diversity and its contribution to shaping an inclusive national identity. The study concludes that Pancasila plays a crucial role in strengthening the sense of unity in the midst of cultural plurality and contributes to the formation of a strong and harmonious national identity.